ANALYSIS OF MARKET INTEGRATION CAYENNE PEPPER (Capsicum frutescens L.) IN MALANG DISTRICT - Artianti Anin Hanani; Ratya Anindita; Rini Mutisari (Agricultural Socio-Economics Journal, 2020)
Cayenne pepper is one of the main food ingredients that is always needed by the people of Indonesia. This makes the compilation of chili prices at the consumer level going up to eliminate losses for farmers, because prices agreed to by consumers are not comparable to the profits obtained by farmers. The price gap that occurs makes farmers not increase. The Purpose this research to analyze the market integrastion and analyze the cayenne reference market. The data used are time series price data during 2014 - 2018. The method of data analysis uses the Error Correction Model (ECM) test and the Engle-Granger Causality test. The application used for data analysis is Eviews 10. The results showed long-term and short-term differences between the price of cayenne There is a one-way relationship while producer prices increase the prices of retailers, so the cayenne reference market is a famers.